2015
DOI: 10.1007/s00455-015-9600-y
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Swallowing Exercises in Head and Neck Cancer Radiotherapy

Abstract: Many head and neck cancer (HNC) survivors experience reduced quality of life due to radiotherapy (RT)-related dysphagia. The aim of this prospective randomized trial was to evaluate the impact of prophylactic swallowing exercises on swallowing-related outcomes in HNC patients treated with curative RT. Patients treated with primary RT for HNC were candidates for this randomized protocol. Participants in the exercise group were instructed to perform swallowing exercises at home. Participants in the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 34 publications
3
67
0
12
Order By: Relevance
“…27 30 In a Danish study of a similar intervention to the current study, an average of 35% of patients reported doing their exercises at least once a day between 1 month and 11 months after treatment. 22 We have therefore selected 35% as the minimum target adherence for our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 30 In a Danish study of a similar intervention to the current study, an average of 35% of patients reported doing their exercises at least once a day between 1 month and 11 months after treatment. 22 We have therefore selected 35% as the minimum target adherence for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recognising the poor patient adherence reported in previous studies of swallowing exercises, 22 24 30 we paid specific attention to optimising patient adherence during the development phase by drawing on theoretical frameworks and tools (The Behaviour Change Wheel, Behaviour Change Technique Taxonomy v1) from the field of behavioural science. 33 34 The new SIP-Swallowing Intervention Package: Self-Monitoring, Assessment, Rehabilitation Training (SIP SMART) was devised using current best evidence of swallowing assessment, 35 as well as insights from our earlier studies exploring the behavioural dimensions of this complex intervention; a systematic review of the literature 36 and a patient interview study (submitted manuscript).…”
Section: Development Of a Tailored Pretreatment Swallowing Interventimentioning
confidence: 99%
See 1 more Smart Citation
“…Not all studies comprehensively delineate their interventions, and often do not report (or only partially report) compliance, which limits the interpretability of their data[25-29]. Among the studies that completely or partially report compliance, the dose and type of interventions vary widely making comparisons on efficacy or dose effect difficult or impossible[30-33]. Coupled with the fact that no dysphagia rehabilitation intervention has been proven efficacious in this patient population, no “acceptable” or “target” dose or frequency of dysphagia rehabilitation therapy exists.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all trials have had positive results [1214], and a number of questions remain, including the optimal timing, selection and duration of exercises, the achievement of intervention fidelity and, importantly, the support necessary to improve adherence [10]. Only 13–14 % of participants practise swallowing exercises as recommended [15, 16].…”
Section: Introductionmentioning
confidence: 99%